Targeted radionuclide therapy: new advances for improvement of patient management and response - Malcolm, J; Falzone, N; Lee, B; Vallis, K (MDPI, 2019)
Compared to external beam radiotherapy, targeted radionuclide therapy (TRT) allows for systemic radiation treatment of metastatic lesions. Published work on recent strategies to improve patient management and response to TRT through individualising patient treatment, modifying treatment pharmacokinetics and increasing anticancer potency are discussed in this review, with a special focus on the application of clinically evaluated radiolabelled ligands and peptides in the treatment of neuroendocrine and prostate cancers.